Ozone Pollution, Health and Well-Being - Julia Rechlitz; Luis Sarmiento; Aleksandar Zaklan (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper evaluates the effect of ozone pollution on individuals' subjective health satisfaction and well-being, allowing us to capture both direct and indirect effects of ozone pollution on adults. Specifically, we focus on differences between households with and without children. We combine geo-coded individual-level data from the German Socio-Economic Panel (SOEP) with data on ozone concentrations from measuring stations in Germany. We precisely assign pollution levels to individuals by exploiting information about the date of the SOEP interview. We find that ozone decreases the well-being of adults sharing households with children, while not causing losses in their own subjective health. The effects are stronger for a greater length of exposure. Our results suggest that damages from ozone in the general population may primarily stem from indirect effects through health effects for children.
Keywords: Q53; Q51; C23; 330; Local pollution; ozone; subjective well-being; subjective health; climate policy co-benefits